(untitled) (Al-Farooq Journal of Sciences, 2026)
This study examined the problem of elections in Libya during the political transition that followed the Arab uprisings, considering elections as one of the main mechanisms for building legitimacy and establishing the foundations of a democratic system. The study aimed to clarify the legal nature of elections, identify their basic principles, analyze international and regional efforts toward the electoral process, and highlight the major obstacles that hinder the success of elections in Libya. The study adopted the descriptive analytical method by describing the political and legal reality and analyzing the factors affecting the electoral path. The findings showed that elections cannot achieve political stability merely by being held; rather, they require a suitable constitutional, security, and institutional environment, as well as national consensus that guarantees acceptance of their results. The study also revealed that political division, weak electoral legislation, lack of trust among parties, foreign interference, and the spread of weapons represent major challenges to building a successful electoral process. The study concluded that it is necessary to address the constitutional vacuum, unify the military institution, enact clear electoral laws, and activate the role of the United Nations in supporting the electoral process and imposing sanctions on obstructing parties, in a way that contributes to a more stable democratic transition and strengthens the chances of building the Libyan state on sound constitutional and institutional foundations.